Level of job satisfaction among tenured and non-tenured teachers in UPV - Faeldonea, Karen Jean
This is a study on the level of job satisfaction among tenured and non-tenured teachers in UPV. The study aims to determine the difference between tenured and non-tenured teachers in their level of satisfaction with regard to the following aspects: nature of work or work itself, pay, and work environment. Seventy-three teachers served as respondents. They indicated their satisfaction according to the aspects using a 5 point Likert type scale. The Job Satisfaction Scale consisted of three factors or aspects that contributed to job satisfaction of teachers at job, namely: work itself, pay, and work environment. The t-test was used to test the null hypotheses that there is no significant difference between tenured and non-tenured teachers in their level of satisfaction on different aspects of job, as to work itself, pay and work environment. The results revealed that the hypotheses of no difference between tenured and non-tenured teachers in their level of satisfaction on different aspects of job, as to work itself, pay, and work environment was supported. Thus, the satisfaction of the tenured and non-tenured teachers in UP Visayas did not differ significantly as to nature of work or work itself, and work environment.